2021
DOI: 10.25115/eea.v39i7.5010
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies in the Organization of Accounting and Control of Calculations for Tax Liabilities of Budgetary Institutions

Abstract: The purpose of the study is to identify areas and form mechanisms for improving the organization of accounting and control of calculations for tax liabilities of budgetary institutions based on the introduction of digital technologies. The relevance of this study is due to the need to solve the problem of modernization of the tax administration system by implementation modern information and analytical resource of the tax service. The study proved that creation of a modern information and analytical resource o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The literature review and the analysis of theoretical approaches to the study of the impact of digital technologies on the organization of control over tax liabilities by budgetary institutions showed that almost all researchers (Bondarenko et al, 2020;Mavlutova et al, 2021;Panasiuk et al, 2021;Prokopenko et al, 2019;Stewart & Clavey, 2021;Syrtseva et al, 2021) are unanimous about the need and inevitability of the transition of fiscal processes to the digital space using artificial intelligence (Mavlutova et al, 2021) and cloud services (Prokopenko et al, 2020;Syrtseva et al, 2021). Therefore, we agree that the use of such services allows the management system to make the calculation of tax liabilities of budgetary institutions transparent and efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review and the analysis of theoretical approaches to the study of the impact of digital technologies on the organization of control over tax liabilities by budgetary institutions showed that almost all researchers (Bondarenko et al, 2020;Mavlutova et al, 2021;Panasiuk et al, 2021;Prokopenko et al, 2019;Stewart & Clavey, 2021;Syrtseva et al, 2021) are unanimous about the need and inevitability of the transition of fiscal processes to the digital space using artificial intelligence (Mavlutova et al, 2021) and cloud services (Prokopenko et al, 2020;Syrtseva et al, 2021). Therefore, we agree that the use of such services allows the management system to make the calculation of tax liabilities of budgetary institutions transparent and efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Globalization of the economic space and popularization of the remote workplace brings the concept of cloud technology to a new level. This concept implies that information is processed not from one computer or workplace but is shared by any number computers connected to the Internet (Syrtseva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the advantages and disadvantages of each of the technologies are not defined. S. Syrtseva analysed digital technologies in the organisation of accounting and control of settlements of tax liabilities [5]. The authors propose to create a modern information and analytical resource of the tax service at the enterprises, which can optimise the accounting and control system.…”
Section: Introductionmentioning
confidence: 99%
“…This study used general interdisciplinary research as the foundation strategy by integrating the discipline of Budgeting, Work performance and organisational compliance to form the framework for the study. This style of the method is a reflection of (Syrtseva et al, 2021). Organisational Compliance: Failure to effectively monitor, identify, investigate, and remedy misbehaviour within an organisation's levels could have disastrous effects.…”
Section: Methodsmentioning
confidence: 99%